High Precision Displacement-Measuring Interferometer Based on Phase Modulation Technique and Modulation Index Instability Elimination - Nguyen, Vu Hai Linh; Vu, Thanh Tung (Old Journal, 2018)
A high precision displacement-measuring interferometer based on a phase modulation technique was developed. A PZT actuator was utilized to drive a mirror of a Michelson interferometer by applying a sinusoidal voltage to the PZT controller. The path difference between two arms of the interferometer was modulated leading to modulation in the phase of the interference signal with a frequency of 3 kHz. The first and second harmonics of the interference signal were detected at the modulation index of 2.63 rad, a special value when the values of the first and second orders of Bessel function are equal. The displacement was determined by the ratio of the second and third harmonic in which the effects of modulation index instability and intensity fluctuation were neglected. Moreover, the direction of the displacement that was ambiguous of the traditional interferometers was clarified in a real time. A measurement precision of 60 nm was obtained using the phase modulation interferometer.